Cycloartane derivatives from Guarea trichilioides - Furlan, Maysa [UNESP]; Roque, Nídia Franca [UNESP]; Filho, Wilson Wolter [UNESP] (Elsevier B.V., 1993)
Investigation of the leaves of Guarea trichilioides afforded nine cycloartane derivatives including the following seven novel ones: cycloart-24-en-. © 1993.
Keywords: Cycloartane derivatives; Guarea trichilioides; Leaves; Meliaceae; Triterpenoids.